2015
DOI: 10.1016/j.renene.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Energy performance evaluation of a marketable net-zero-energy house: Solark I at Solar Decathlon China 2013

Abstract: a b s t r a c tThis paper presents the energy performance evaluation of a marketable net-zero-energy house (NZEH): Solark I at Solar Decathlon China 2013. The assessment methodologies are based on EnergyPlus simulations and measured data. The paper also discusses the reasons for the differences between the results of the simulations and the measurements, analyzes the investment cost, summarizes the lessons learned from the competition, and presents the potential for replicability and transposition from Solark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Because it is necessary to comply with the relevant regulations of China's highway transportation safety regulations, the 12meter-long IAA container consumes a lot of money and time in the transportation process. Furthermore, due to the temporarily dispatched for on-site construction, they are still not completed on time [9]. Not only that, but also based on the preconditions for ensuring the safe use of container houses, relevant regulations have made corresponding restrictions on the side window opening dimensions and building height of the container according to the structural characteristics of the container itself.…”
Section: Transport and Constructionmentioning
confidence: 99%
“…Because it is necessary to comply with the relevant regulations of China's highway transportation safety regulations, the 12meter-long IAA container consumes a lot of money and time in the transportation process. Furthermore, due to the temporarily dispatched for on-site construction, they are still not completed on time [9]. Not only that, but also based on the preconditions for ensuring the safe use of container houses, relevant regulations have made corresponding restrictions on the side window opening dimensions and building height of the container according to the structural characteristics of the container itself.…”
Section: Transport and Constructionmentioning
confidence: 99%
“…As prior studies related to NZEHs have shown, several simulations have been conducted to achieve net-zero energy through a combination of energy-efficient technology and renewable energy. Optimizing the design of building envelopes (insulation and windows, airtightness performance, and more) for the load reduction in residential buildings [4][5][6][7][8][9][10][11][12] is one way to achieve this. Baek et al analyzed energy usage for six houses of the same shape, size, and renewable energy system located in Daejeon, Korea, which were designed with the object of net-zero as empirical cases of NZEHs.…”
Section: Introductionmentioning
confidence: 99%
“…The version of the competition, Solar Decathlon Latin America and Caribbean 2015 (Cali, Colombia), to which the prototype presented in this article was submitted, unlike previous editions [8][9][10][11][12][13], was given a social approach, which allowed researching on other architectural typologies and sustainable-healthy construction solutions, where the transfer to society of the environmental strategies implemented in these prototypes gained special relevance. The objective was no longer to present a housing cell where excellent comfort conditions and minimum energy consumption were achieved on the basis of technology decontextualized socioeconomically from the society where the competition was held [14].…”
Section: Introductionmentioning
confidence: 99%